Boosting Performance Through Work Discipline: The Role of Transformational Leadership and Motivation in the Context of the Indonesian Air Force Military - Abdur Rachman Alkaf; Eddy Yunus; Sri Utami Ady (Yayasan Riset dan Pengembangan Intelektual, 2023)
The Indonesian National Air Force (TNI AU), as an integral part of the Indonesian National Armed Forces (TNI), is a crucial component of Indonesia's air power. It is essential to enhance the performance of officers, and one way to monitor and evaluate their performance can be seen through the promotion rate. However, there was a decline in officer rank promotions from 2017 to 2019. In 2020, there was an increase, but the difference compared to 2018 was not significant. This indicates a decrease in officer performance from 2017 to 2021. This decline should be a concern for organizational leaders and a target for strategic planning to discover new strategies for enhancing the effectiveness of officer performance. The study examined the impact of transformational leadership and motivation on officer performance through work discipline. The research was quantitative with the population in this study consists of all Indonesian Air Force officers, totaling 10,295. Nonprobability sampling was used and purposive sampling was employed with specific criteria. Based on the calculation used Slovin formula, the sample size was 400 officers. Data analysis used a Structural Equation Model (SEM) framework with Partial Least Squares Structural Equation Model (PLS-SEM) which is the statistical method employed to analyze the relationships among latent variables within the Structural Equation Model (SEM) framework. The test include measurement and structura model (outer-inner model) and used Smart PLS version 3.2.9 as a tool for analysis. The result from this research found that transformational leadership, motivation, and discipline influence on officer performance, transformational leadership and motivation influence on discipline, and discipline mediate the relationship of transformational leadership and motivation on officer performance. The implication can assist the Air Force in designing better human resource management strategies, improving officer performance, and achieving their operational objectives more effectively.